Bullous eruptions in a preschool child: A rare adverse effect of acyclovir - Nidhi Garg; K V Vinu Balraam (Wolters Kluwer Medknow Publications, 2020)
Acyclovir in children is usually associated with minimal local adverse effects, with bullous eruptions being extremely rare in occurrence. A 5-year-old boy was admitted to the pediatric intensive care unit as a case of febrile encephalopathy with status epilepticus. He was managed empirically with intravenous antibiotics and antiviral drugs (acyclovir). On day 6, he developed hemorrhagic bullae near the infusion site, which reappeared after every acyclovir infusion. No definitive cause was identified despite thorough hematological, serological, and microbiological investigations. After a meticulous literature search and application of Naranjo algorithm, acyclovir was found to be the definitive cause of the bullous eruptions.